Reduction of unwanted submental fat with ATX‐101 (deoxycholic acid), an adipocytolytic injectable treatment: results from a phase III, randomized, placebo‐controlled study. (18th February 2014) - Rzany, B.; Griffiths, T.; Walker, P.; Lippert, S.; McDiarmid, J.; Havlickova, B.
Summary: Background: Unwanted submental fat (SMF) is aesthetically unappealing, but methods of reduction are either invasive or lack evidence for their use. An injectable approach with ATX‐101 (deoxycholic acid) is under investigation. Objectives: To evaluate the efficacy and safety of ATX‐101 for the reduction of unwanted SMF. Methods: In this double‐blind, placebo‐controlled, phase III study, 363 patients with moderate/severe SMF were randomized to receive ATX‐101 (1 or 2 mg cm −2 ) or placebo injections into their SMF at up to four treatment sessions 28 days apart, with a 12‐week follow‐up. The co‐primary efficacy endpoints were the proportions of treatment responders [patients with ≥ 1‐point improvement in SMF on the 5‐point Clinician‐Reported Submental Fat Rating Scale (CR‐SMFRS)] and patients satisfied with their face and chin appearance on the Subject Self‐Rating Scale (SSRS). Secondary endpoints included skin laxity, calliper measurements and patient‐reported outcomes. Adverse events were monitored. Results: Significantly more ATX‐101 recipients met the primary endpoint criteria vs. placebo: on the clinician scale, 59·2% and 65·3% of patients treated with ATX‐101 1 and 2 mg cm −2, respectively, were treatment responders vs. 23·0% for placebo (CR‐SMFRS; P < 0·001); on the patient scale, 53·3% and 66·1%, respectively, vs. 28·7%, were satisfied with their face/chin appearance (SSRS; P < 0·001). Calliper measurements showed a significant reduction in SMF ( P < 0·001), skin laxity was not worsened and patients reported improvements in the severity and psychological impact of SMF with ATX‐101 vs. placebo. Most adverse events were transient and associated with the treatment area. Conclusions: ATX‐101 was effective and well tolerated for nonsurgical SMF reduction. Abstract : What's already known about this topic? Unwanted submental fat (SMF) is considered aesthetically unappealing. Liposuction and face‐lift are effective treatments for SMF reduction but are invasive and not suitable for all patients, whereas nonsurgical alternatives lack robust clinical evidence related to their safety and efficacy. ATX‐101, a proprietary formulation of synthetically derived deoxycholic acid, is the first nonsurgical treatment for SMF reduction to be investigated in randomized, placebo‐controlled clinical studies. What does this study add? This study provides the first data from a large‐scale, randomized, placebo‐controlled, phase III study of an injectable therapy for SMF reduction in a field currently lacking a sound evidence base. ATX‐101 was superior to placebo for the clinician‐ and patient‐evaluated reduction of unwanted SMF and led to improved patient perception about their appearance. ATX‐101 was well tolerated; treatment‐associated adverse events were mainly transient and localized injection‐site reactions.